Amyloid-Beta induces endothelial endoplasmic reticulum stress in association with blood-brain barrier disruption in experimental models of Alzheimer's disease - Pomilio, Carlos Javier (2020)
Alzheimer's disease (AD) is the leading cause of dementia. Among other histopathological hallmarks, it is characterized by the abnormal accumulation of Amyloid-β (Aβ) peptides. Vascular alterations and blood-brain barrier disruption are also evidenced in AD patients, in close association with perivascular amyloid deposits, which are composed mainly of Aβ 1-40. In this study we characterized the progression of vascular alterations in the hippocampus of PDAPP-J20 mice, a validated transgenic model for AD.